Data leak, critical information infrastructure and the legal options: what does Wikileaks teach us? - Abdul Ghani Azmi, Ida Madieha; Zulhuda, Sonny; Jarot, Sigit Puspito Wigati (The Society of Digital Information and Wireless Communications (SDIWC), 2012)
The massive data leaks by Wikileaks suggest how fragile a national security is from the perspective of information system and network sustainability. What Wikileaks have done and achieved raises some causes of concern. How do we view such leaks? Are they an act of whistle-blowing or disclosure of government misconduct in the interest of the public? Are they the champion of free press? Or are they a form of data breach or information security attack? What if it involves the critical information infrastructure (CII)? Could they be classified as ‘cyber-terrorist’? The objective this paper is to outline the problems and challenges that Malaysia should anticipate and address in maintaining its national CII. The paper first looks at Wikileaks as it is the ‘icon’ of data leaks. Then it examines the causes of data breach before proceeding to foray into the concept of ‘critical information infrastructure’ in the US and Malaysia. Finally, the paper explores legal options that Malaysia can adopt in preparing herself to possible data breaches onslaught. It is the contention of the paper that the existing traditional legal framework should be reformed in line with the advances of the information and communications technologies, especially in light of the onslaught of data leaks by the new media typically represented by Wikileaks.